2012
DOI: 10.3389/fnbeh.2012.00020
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Broad Versus Segregated Projections from Cholinergic and Noradrenergic Nuclei to Functionally and Anatomically Discrete Subregions of Prefrontal Cortex

Abstract: The prefrontal cortex (PFC) is implicated in a variety of cognitive and executive operations. However, this region is not a single functional unit; rather, it is composed of several functionally and anatomically distinct networks, including anterior cingulate cortex (ACC), medial prefrontal cortex (mPFC), and orbitofrontal cortex (OFC). These prefrontal subregions serve dissociable behavioral functions, and are unique in their afferent and efferent connections. Each of these subregions is innervated by ascendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 81 publications
(110 reference statements)
4
79
0
Order By: Relevance
“…Wide-ranging evidence indicates the importance of galanin in noradrenergic neurons and possible functional differences between galanergic and non-galanergic LC neurons (Sevcik et al, 1993;Miller et al, 1999;Sciolino et al, 2015). However, despite evidence that the LC contains neurons with distinct projection profiles (Chandler and Waterhouse, 2012;Chandler et al, 2013Chandler et al, , 2014, the subpopulations distinguished by Gal-Cre expression show no gross difference in their axonal targets. This surprising result is compatible with the recently reported finding that specifically activating the Gal-Creexpressing LC subpopulation has the same effect on aversive behavior as activating the whole LC (McCall et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wide-ranging evidence indicates the importance of galanin in noradrenergic neurons and possible functional differences between galanergic and non-galanergic LC neurons (Sevcik et al, 1993;Miller et al, 1999;Sciolino et al, 2015). However, despite evidence that the LC contains neurons with distinct projection profiles (Chandler and Waterhouse, 2012;Chandler et al, 2013Chandler et al, , 2014, the subpopulations distinguished by Gal-Cre expression show no gross difference in their axonal targets. This surprising result is compatible with the recently reported finding that specifically activating the Gal-Creexpressing LC subpopulation has the same effect on aversive behavior as activating the whole LC (McCall et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our proof-of-principle application of RC::FLTG and RC::RFLTG to analysis of the central noradrenergic system confirms the value of key features of these alleles. There are no molecular markers known to uniquely label subpopulations of noradrenergic neurons, so investigation of noradrenergic neuron heterogeneity, particularly axon projection patterns, depends either on genetic intersectional labeling (Robertson et al, 2013) or strategies for retrograde labeling by injection of dyes or viruses at target sites (Chandler and Waterhouse, 2012;Chandler et al, 2013Chandler et al, , 2014Schwarz et al, 2015). The ability of RC::FLTG to label axons of the entire noradrenergic system, subdivided between an intersectional and a subtractive population, reveals diversity of noradrenergic projections at target sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest population of relaxin-3 expressing neurons is located within the tegmental area known as the nucleus incertus (NI), and these neurons project broadly throughout the brain [15][16][17][18][19]. The neuroanatomy of the relaxin-3/RXFP3 system suggests a broad role as an ascending neuromodulatory network [20,21], akin to the monoamine systems including serotonin, and noradrenaline [22][23][24][25]. Anatomical and functional data [15][16][17][18] suggest that relaxin-3/RXFP3 systems may interact directly with monoamine [19,26] and other peptide systems [27][28][29], and/or act at shared downstream limbic and hypothalamic target areas to modulate 'anxiety' and other stress-related responses [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Using this type of approach, several studies found a high degree of heterogeneity in LC neurons with respect to their efferent connectivity. One study injected three different fluorescent retrograde tracers into the orbitofrontal cortex (OFC), mPFC, and anterior cingulate cortex (ACC) (Chandler and Waterhouse 2012). Interestingly, largely nonoverlapping cell populations projecting to these three regions were detected in the LC.…”
Section: Anatomical Connectivity and Efferent Specificity In Lc Neuronsmentioning
confidence: 99%